2013
DOI: 10.5012/bkcs.2013.34.10.3033
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled Chevrel Mo6S8as Cathode Material for Mg Rechargeable Battery

Abstract: Nanoscale Chevrel Mo6S8 powders are synthesized by molten salt synthesis. Synthesized Mo6S8 powders have different mean particle sizes which are dependent on a ratio of salt to precursor. The particle sizes of Mo6S8 powders changes along with the ratio increase. Mo6S8 (6:1) demonstrates the best electrochemical characteristics among the synthesized Mo6S8 powders although the Mo6S8 (4:1) has the smallest particle size. Mo6S8 (6:1) shows a reversible capacity of 83.9 mAhg −1 , which is 27.5% and 33% improved val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…CP nanofibers with diameters in the 100-300 nm range have also been synthesized from a solgel technique, although their electrochemical performance has not be reported [146]. Ryu et al [148] also found that controlling the ratio of KCl salt to precursor material in a molten salt synthetic reaction can be used to control the size and electrochemical properties of the product CP. Median diameters of 0.24, 0.57 and 0.75 μm were obtained for 4:1, 6:1 and 2:1 salt-to-precursor ratios (whether this is a weight or molar ratio was not specified).…”
Section: Cathode Materialsmentioning
confidence: 99%
“…CP nanofibers with diameters in the 100-300 nm range have also been synthesized from a solgel technique, although their electrochemical performance has not be reported [146]. Ryu et al [148] also found that controlling the ratio of KCl salt to precursor material in a molten salt synthetic reaction can be used to control the size and electrochemical properties of the product CP. Median diameters of 0.24, 0.57 and 0.75 μm were obtained for 4:1, 6:1 and 2:1 salt-to-precursor ratios (whether this is a weight or molar ratio was not specified).…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Ryu et al investigated the relationship between Mo 6 S 8 particle size and the ratio of KCl salt with precursors. 25 Increasing the ratio of KCl melting salt from 1:1 to 4:1 decreased the particle size of CP from 0.75 to 0.24 μ m. Consequently, the initial discharge capacity changed from 73 to 85 mAh/g. Saha et al also tried to control the particle size through a co-precipitation method followed by a conventional calcination process.…”
Section: Chevral Phasementioning
confidence: 95%
“…Other peaks also shift according to the triclinic structure (32°−48°graph of Figure 2c). 17,33 These structures have different bond lengths and angles depending on the distance between the Mo−Mo and Mo−S bonds, which form a system of open three-dimensional networks. In particular, the Mo 6 cluster, which has the form of an elongated octahedron with −3 symmetry in trigonal systems (rhombohedral and hexagonal structure), shows triclinic deformation in the triclinic phase transition.…”
Section: Characterization Of Cu 18 Mo 6 S 8 (Cu-cp)mentioning
confidence: 99%